2022
DOI: 10.1136/jim-2021-002008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 attenuates renal injury after myocardial infarction in diabetes

Abstract: Acute kidney injury (AKI) is a common complication after myocardial infarction (MI) and associated with significant morbidity and mortality. AKI after MI occurs more frequently in patients with diabetes, however, the underlying mechanisms are poorly understood, and specific treatments are lacking. Using the murine MI model, we show that diabetic mice had higher expression of the kidney injury marker, neutrophil gelatinase-associated lipocalin (NGAL), 3 days after MI compared with control mice. This higher expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Katherine et al con rmed that primary ADPKD or NHK cells promote macrophage conversion to a distinct M2-like phenotype (16). In the present study, we revealed that RTECs were indispensable for M1-to-M2 transition of renal macrophages and that RTECs signi cantly upregulate the expression of IL-10 in the renal macrophages, which further stimulated RTEC proliferation (40). Some of the limitations of this study are as follows.…”
Section: Discussionmentioning
confidence: 74%
“…Katherine et al con rmed that primary ADPKD or NHK cells promote macrophage conversion to a distinct M2-like phenotype (16). In the present study, we revealed that RTECs were indispensable for M1-to-M2 transition of renal macrophages and that RTECs signi cantly upregulate the expression of IL-10 in the renal macrophages, which further stimulated RTEC proliferation (40). Some of the limitations of this study are as follows.…”
Section: Discussionmentioning
confidence: 74%
“…There is an increasing amount of evidence showing that the PI3K/AKT 55 , TGF‐β 56 , Notch 57 and Wnt pathways 58 are activated during DN development. IL‐10 polymorphism was elucidated as a protective factor for DN 59 , as it reduced acute inflammation and fibrosis in the kidneys of diabetic mice 60 . Evidence supports the activation of IL‐17A, which aggravates kidney injury in DN 61 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that IL-10 is an important inflammatory suppressor in the body and is implicated in the development and progression of cardiovascular diseases. Several basic experiments demonstrated that IL-10 can promote myocardial repair, inhibit cardiac remodeling, and ameliorate functional impairment of other important organs after AMI [ 26 27 28 ]. Based on the findings from the present study and previous experiments, we suggested that IL-10 was likely to prevent the development of AMI; following the disease, the inflammatory factor might in turn be upregulated in a feedback manner, serving to promote repair and improve prognosis.…”
Section: Discussionmentioning
confidence: 99%